Analisis dan Pengujian Perangkat Lunak Sistem Informasi Pembayaran Sekolah dengan Metode Pengukuran Kualitas SQuaRE - Rahman Abdillah; Rudi Hermawan; Wawan Hermawansyah; Dwi Puspita Agustin; Ibnu Adkha; Nur Alam (Pusat Riset dan Inovasi Nasional, 2025)
Software quality testing is a crucial stage in the development of information systems to ensure their reliability and functionality. This study aims to analyze and test the software quality of the School Payment Information System using the Software Product Quality Requirements and Evaluation (SQuaRE) method. This method refers to the ISO/IEC 25000 standard, which measures various aspects of software quality, including functionality, reliability, efficiency, compatibility, usability, security, maintainability, and portability. The aim of this research was conducted through a series of tests by collecting data from system specifications, test designs, and user feedback. The test results indicate that the evaluated information system meets most of the quality indicators based on the SQuaRE standard, with some aspects still requiring improvement, particularly in terms of usability and system efficiency. This evaluation provides deeper insights into the effectiveness of applying the SQuaRE method in software testing and offers recommendations for improving system quality. Thus, the implementation of the SQuaRE method is expected to enhance the reliability and efficiency of the school payment information system, thereby supporting more effective and accurate financial management in schools.